pH induced stress enhances lipid accumulation in microalgae grown under mixotrophic and autotrophic condition - Alkhamis, Yousef Ahmed; Mathew, Roshmon Thomas; Nagarajan, Ganesan; Rahman, Sheikh Mustafizur; Rahman, Md. Moshiur (Frontiers in Energy Research, 2022)
Production of biodiesel along with wastewater treatment and CO2 sequestration is a promising technology. Rising concentrations of atmospheric CO2 results in higher concentrations of dissolved CO2 in natural waters, which leads to increase in hydrogen ion and bicarbonate concentrations and decrease in hydroxyl ion and carbonate concentrations. These climate change effects are the dynamic nature of carbon cycling in coastal zones, which can lead to seasonal and diel changes in pH and CO2 concentrations that can exceed changes expected for open ocean ecosystems. Studies were conducted to examine the effects of various pH levels on algal growth and lipid production in order to better understand how the growth of algae may be influenced in such conditions. In present study the influence of three different pH (6, 8 and 10) was studied to evaluate microalgae's carbohydrate utilisation and lipid accumulation during the operation’s starvation phase (SP). Microalgae in the study were cultivated in two modes viz., mixotrophic [growth phase (GP)] and autotrophic [pH-induced (SP)] conditions. Enhancement in biomass formation, intracellular carbohydrate accumulation was recorded during the GP operation, while noticeable lipid productivities (Total/neutral, 26.93/10.3%) were observed during SP operation at pH 8. Pigment analysis showed variations in both procedures where higher Chl a concentration was noticed in GP, and higher Chl b was detected during SP. Nile red fluorescent staining strongly supports the existence of intracellular lipid bodies (LB). GC analysis of fatty acid methyl esters (FAME) showed a more significant number of saturated fatty acids (SFA) than unsaturated fatty acids (USFA). Efficient wastewater treatment with nutrient assimilation was registered during GP operation, indicating the phyco-remediation.